Uso de fluoresceína sódica em meningeomas da base do crânio - Silva, Carlos Eduardo da (2013)
Objective: The authors present a study with the use of sodium fluorescein (SF) to enhance skull base meningiomas and perform a quantitative digital analysis of the tumors enhancement. The study intends to observe the grade of cranial base meningiomas enhancement by SF. Methods: A prospective within-subjects study was performed including twelve patients with skull base meningiomas. Digital pictures were obtained before and after the SF systemic injection, using the same light-source of the microsurgical field. The pictures were analyzed by Image Pro Plus 4.5.1 software, which calculated the wavelength of the sodium fluorescein pre and post injection. Results: The group of meningiomas was composed as it follows: one cavernous sinus, one olfactory groove, three petroclival, one tuberculum sellae, three sphnoid wing, one anterior clinoid and two temporal floor. The SF enhancement in all tumors was strongly positive. The digital analysis of the pictures, considering the SF wavelength pre and post injection, presented p=0.002 (Wilcoxon T test). Conclusions: The enhancement of the skull base meningiomas by SF was consistent. The introductory results suggest the possibility of using SF as an adjuvant tool for the skull base meningioma surgery. Further studies should test the clinical application of the SF in skull base tumors.